Establishment of baseline size-specific dose estimate (SSDE) for paediatric head computed tomography (CT) examinations - Hamza Sulemana; Abdul Nashirudeen Mumuni; Izre-deen Osman Mohammed Abubakari (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background In recent times, size-specific dose estimate (SSDE) has been the ideal metric for accurate estimation of individual patient doses in computed tomography (CT) examinations. The objective of this study was to estimate patient radiation doses based on SSDE and the water-equivalent diameter (D W ) as an effect tool for dose optimization in paediatric head CT at two facilities in Tamale Metropolis, in the northern region of Ghana. This is a preliminary retrospective study conducted on 57 paediatric patients (comprising 32 males and 25 females), aged newborns to 16 years old, who underwent head CT examinations. Patient head sizes were determined in terms D W , which was calculated by manual contouring the circumference of the CT images excluding the background to measure the region of interest (ROI) using the mid-slice axial CT images. SSDE was calculated as the product of CTDIvol and the size-specific conversion coefficients (CTDIvol, 16 to SSDE) obtained from the American Association of Physicists in Medicine (AAPM) Report 293. Results At facility ‘A’, the median SSDE values for patients, aged 3 months to 1 year, 1 to 6 years, and older than 6 years were 46.1 mGy, 39.6 mGy, and 48.2 mGy, respectively. The corresponding CTDIvol values were 42.3 mGy, 39.1 mGy, and 51.7 mGy. Facility ‘B’ reported median SSDE values of 36.0, 39.2, and 43.8 mGy, with corresponding CTDIvol values of 28.7, 39.8, and 46.9 mGy for the same age categories. For all age groups, the two facilities showed significant differences in SSDE values (44.72 mGy vs. 39.77 mGy, p = 0.009) and CTDIvol values (45.72 mGy vs. 40.60 mGy, p = 0.03). Some of the age group doses were up to 25.3% in CTDIvol and 25.8% in SSDE higher than those found in published data. Conclusions The SSDEs estimated showed significant variations between the two facilities, indicating a possible variability of scan protocols for paediatric head CT examinations. The SSDEs obtained in this study could be useful for optimization of paediatric routine head CT examinations.